DOI: 10.25148/etd.fi14062277
|View full text |Cite
|
Sign up to set email alerts
|

Predicting employee compliance with safety regulations, factoring risk perception

Abstract: The purpose of this research was to develop a methodology that would evaluate employees' personality traits, demographic characteristics, and workplace parameters to predict safety compliance along with the moderating effect of risk perception. One hundred and twenty five employees of a manufacturing facility were given questionnaires to gather their demographic and perception information. Surveys were also used to measure their personality characteristics, and periodic observations were recorded to document e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…However, it is worth mentioning that the main people carrying out training are the managers. In addition, the construction workers themselves have a low level of education, so the construction workers alone can hardly achieve a highly engaging training [ 87 ]. Zhao et al [ 88 ] revealed that the participation of senior managers played a positive role in the implementation of risk management.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…However, it is worth mentioning that the main people carrying out training are the managers. In addition, the construction workers themselves have a low level of education, so the construction workers alone can hardly achieve a highly engaging training [ 87 ]. Zhao et al [ 88 ] revealed that the participation of senior managers played a positive role in the implementation of risk management.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Workers who scored high on the risk-taking module of the JPl-R were less likely to comply with company PPE requirements than those who scored low on the scale. For a full statistical analysis ofthese results, see Diaz (2000).…”
Section: Relationship Between Personality and Compliancementioning
confidence: 99%